Use of colposcopy in diagnosing early dysplastic changes in oral premalignant condition - Surekha Rathod; Ishita Wanikar; Abhay P Kolte; Shweta Maske; Sulbha Joshi; Vivek Harkare (Wolters Kluwer Medknow Publications, 2017)
Purpose: Areca nut, a suspected human carcinogen, is responsible for oral submucous fibrosis (OSMF). Micro colposcopy, a noninvasive technique, can be used for early detection of dysplastic changes in the oral tissues. The aim of this study was to evaluate and compare the effect of areca nut on oral mucosa in healthy controls and those with OSMF using a colposcope. Materials and Methods: The study was conducted on participants with a habit of chewing areca nut and suffering from OSMF. 2% acetic acid was applied on the parts of the gingiva and oral mucosa kept for 2 min and viewed under the colposcope. After a few minutes, Lugol's iodine solution was applied and reviewed under the colposcope. Results: All clinical parameters were higher in Group III (areca nut chewers with OSMF) and Group II (areca nut chewers without OSMF) as compared to Group I (healthy controls) (P < 0.05). Conclusion: Colposcope could aid in the visualization of the changes developed in oral mucosa as an effect in the vasculature of the gingiva.